Future marginalisation and mortality in young Swedish men with non-psychotic psychiatric disorders and the resilience effect of cognitive ability: a prospective, population-based study. Issue 8 (10th August 2016) - Löve, J; Hensing, G; Söderberg, M; Torén, K; Waern, M; Åberg, M
Abstract : Objective: Large-scale studies examining future trajectories of marginalisation and health in adolescents with mental illness are scarce. The aim of this study was to examine if non-psychotic psychiatric disorders (NPDs) were associated with future indicators of marginalisation and mortality. We also aimed to determine whether these associations might be mediated by education level and attenuated by high cognitive ability. Design: This is a prospective cohort study with baseline data from the Swedish Conscription register. Setting: The study was carried out in Sweden from 1969 to 2005. Participants: All of the participants were 18-year-old men at mandatory conscription in Sweden between 1969 and 2005 (n=1 609 690). Measures: NPDs were clinically diagnosed at conscription. Cognitive ability was measured by a standardised IQ test at conscription. National register data covered information on welfare support, long-term unemployment, disability pension (DP) and mortality over a period of 1–36 years. Results: NPD at the age of 18 years was a predictor of future welfare support, OR 3.73 (95% CI 3.65 to 3.80); long-term unemployment, OR 1.97 (95% CI 1.94 to 2.01); DP, HR 2.95 (95% CI 2.89 to 3.02); and mortality, HR 2.45 (2.33–2.52). The adjusted models suggested that these associations were not confounded by fathers' educational level, cognitive ability had only a minor attenuating effect on most associations and the mediating effect of own educational level was small. Conclusions: The present study underlines a higher prevalence of future adversities in young men experiencing NPDs at the age of 18 years. It also indicates that higher cognitive ability may work as a potential resilience factor against future marginalisation and mortality.